Indicators for the sustainability assessment of MBR technologies for wastewater reuse in Chile: The good, the bad, and the ugly - Montserrat Rodríguez-Castillo; Vanessa Bolívar-Paypay; Witold-Roger Poganietz; Ana Lucía Prieto (MethodsX, 2023)
While Chile faces a mega-drought, wastewater reuse emerges as an alternative solution. In this study we develop a set of indicators for the comprehensive sustainability assessment for the application of advanced wastewater treatment technologies (e.g., MBRs) in a wastewater reuse project in Chile. The methodology is based on the Integrative Concept of Sustainable Development (ICoS) framework. A critical analysis of the set of indicators is presented in terms of the benefits (The Good), the difficulties (The Bad), and the barriers (the Ugly) for their development and potential application. The characterization of the environmental benefits constitutes the useful aspects (e.g., recovery of nutrients, energy, and water). Difficulties include economic aspects (e.g., continuous monitoring of emerging contaminants) and public acceptance. Political and administrative aspects were found to be the main barrier, including water rights in Chile and the absence of a clear regulatory framework for wastewater reuse. To our knowledge, this study is the first to present a detailed methodology for developing indicators for membrane-based water reuse projects in Chile.The steps to develop the indicators are: • Identification of the study zone or case study, characterization of treatment technology. • Identification and formulation of indicators for the specific case study, based on the ICoS framework. • Verification of the relevance of indicators for the case study according to data availability and expert reviews.